1983
DOI: 10.7164/antibiotics.36.365
|View full text |Cite
|
Sign up to set email alerts
|

Biological conversion of erythronolide B,an intermediate of erythromycin biogenesis,into new "hybrid" macrolide antibiotics.

Abstract: Transformation of erythronolide B to new antibiotics was attempted by feeding this compound during the fermentation of Streptomyces antibioticus ATCC 31771, a blocked mutant of an oleandomycin producing strain. As a result, four new active compounds were obtained with hybrid structures between erythromycin and oleandomycin. They were identified as 3-O-oleandrosyl-5-O-desosaminyl-15-hydroxyerythronolide B (I), 3-O-oleandrosyl-5-Odesosaminylerythronolide B (H), 3-O-oleandrosyl-5-O-desosaminyl-(8S)-8-hydroxyeryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Additional C-3-appended sugars observed include 4′- O -acetyl-αL-arcanose ( 122b ) [and corresponding engineered 2′,3′-anhydro-arcanose ( 182 ) and 3′-acetylated 180 657,658 ] of the lankamycins 659 and the kujimycins [which contain a C-3 α-L-arcanose ( 122a ) or 4′- O -acetyl-α-L-arcanose ( 122b ) and a C-5 β-D-lankavose ( 181b )] 660 and α-L-oleandrose ( 184 ); found in oleandomycin 647,661 and the 3- O -oleandrosyl-5- O -desosaminyl-(8 S )-8-hydroxyerythronolide B 662 from bioconversion. Additional sugars attached to C-5 include 3-keto-4,6-dideoxy-β-D-hexopyranose 179 (CP-63693 640 ), β-D-chalcose ( 181b ; lankamycins 659 and kujimycins 654 ) and β-D-mycaminose ( 185 ; narbolide, 663 via biotransformation).…”
Section: Macrolides and Macrolactamsmentioning
confidence: 99%
“…Additional C-3-appended sugars observed include 4′- O -acetyl-αL-arcanose ( 122b ) [and corresponding engineered 2′,3′-anhydro-arcanose ( 182 ) and 3′-acetylated 180 657,658 ] of the lankamycins 659 and the kujimycins [which contain a C-3 α-L-arcanose ( 122a ) or 4′- O -acetyl-α-L-arcanose ( 122b ) and a C-5 β-D-lankavose ( 181b )] 660 and α-L-oleandrose ( 184 ); found in oleandomycin 647,661 and the 3- O -oleandrosyl-5- O -desosaminyl-(8 S )-8-hydroxyerythronolide B 662 from bioconversion. Additional sugars attached to C-5 include 3-keto-4,6-dideoxy-β-D-hexopyranose 179 (CP-63693 640 ), β-D-chalcose ( 181b ; lankamycins 659 and kujimycins 654 ) and β-D-mycaminose ( 185 ; narbolide, 663 via biotransformation).…”
Section: Macrolides and Macrolactamsmentioning
confidence: 99%
“…Later on, two 6-deoxysugars (L-oleandrose and D-desosamine) are attached to the aglycon. As late steps, C8 hydroxylation and epoxide formation occur after the transfer of the two sugar residues onto the macrolactone (Spagnoli et al 1983). Several genes of the oleandomycin biosynthetic pathway have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the mutant was generated by gene disruption, a polar effect preventing the expression of oleG2 could not be excluded. It has been previously demonstrated that cross‐feeding with erythronolide B, during the fermentation of an S. antibioticus mutant strain blocked in the synthesis of the macrolactone ring, resulted in the transfer of l ‐oleandrose and d ‐desosamine to the erythronolide B lactone substrate (Spagnoli et al ., 1983). These results indicated that erythronolide B was accepted as an alternative substrate by the two glycosyltransferases of S. antibioticus , and analysis of the hybrid compounds produced demonstrated that C‐8 hydroxylation and epoxide formation were taking place after the transfer of both sugars in the course of oleandomycin biosynthesis (Spagnoli et al ., 1983).…”
Section: Introductionmentioning
confidence: 99%